1997
DOI: 10.1159/000310760
|View full text |Cite
|
Sign up to set email alerts
|

Severe Myopia as a Risk Factor for Progressive Visual Field Loss in Primary Open-Angle Glaucoma

Abstract: The optic nerve head in severely myopic eyes may be particularly vulnerable to glaucomatous damage. To study this hypothesis, we examined 122 primary open-angle glaucoma eyes with fair to good control of the intraocular pressure and a sign of baseline optic nerve damage. Then, parameters for the progression of the visual field defects were evaluated by multivariate analysis. A high mean intraocular pressure (p = 0.007) and a large refractive error (p = 0.023) were significant risk factors for subsequent visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
2
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(99 citation statements)
references
References 28 publications
3
91
2
3
Order By: Relevance
“…It disagrees with findings from the Los Angeles Latino Eye Study [45]. The correlation between hyperopia and lower intraocular pressure, or in other words the correlation between myopia and higher intraocular pressure, does not explain the association between myopia and glaucoma as described in the Beijing Eye Study and other investigations [30,[46][47][48], since the multivariate analysis included intraocular pressure as a potentially confounding factor. Our study therefore confirms previous population-based studies and hospital-based investigations on the association between glaucoma and high myopia [30,[46][47][48].…”
Section: P-valuecontrasting
confidence: 75%
“…It disagrees with findings from the Los Angeles Latino Eye Study [45]. The correlation between hyperopia and lower intraocular pressure, or in other words the correlation between myopia and higher intraocular pressure, does not explain the association between myopia and glaucoma as described in the Beijing Eye Study and other investigations [30,[46][47][48], since the multivariate analysis included intraocular pressure as a potentially confounding factor. Our study therefore confirms previous population-based studies and hospital-based investigations on the association between glaucoma and high myopia [30,[46][47][48].…”
Section: P-valuecontrasting
confidence: 75%
“…A prospective study of untreated NTG (Drance et al 2001) and retrospective studies of untreated NTG (Araie et al 1994) or treated NTG (Ishida et al 1998(Ishida et al , 2000Sohn et al 2010) all failed to find a significant association of further progression and myopia. Regarding high myopia, two studies showed that it was a risk factor for the progression of VF in treated POAG patients (Chihara et al 1997;Perdicchi et al 2007). However, high myopia may differ from nonhighly myopic eyes not only in refractive error, but also in pathology (Curtin 1985b;Jonas & Dichtl 1997;Jonas et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice it is relevant to evaluate the RNFL of myopic eyes because myopia is a well-known risk factor for occurrence and progression of primary open-angle glaucoma [24,25,26]. The outcome of this study shows that myopic eyes are not different from emmetropic eyes in terms of RNFL thickness, as assessed by many SLP parameters; in addition, in some cases RNFL thickness seems to be higher in myopic eyes (TSNIT average, Superior average, Ellipse average, Symmetry).…”
Section: Discussionmentioning
confidence: 99%